2003
DOI: 10.1016/s0920-5632(03)01331-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrinoless double beta decay: Present and future

Abstract: Present status, and future plans for Double Beta Decay searches are reviewed. Given the recent observations of neutrino oscillations, a possibility to observe ββ(0ν) at a neutrino mass scale suggested by present experimental results (mν ≈10-50 meV) could actually exist. The achievement of the required experimental sensitivity is a real challenge faced by a series of new proposed projects. Plans to achieve such a result are described.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Recent works have been given in recent review articles, [1][2][3][4][5][6] and references therein. Recent experimental INVITED REVIEW PAPERS works have also been given in recent conference reports by Fiorini,17) Cremonesi, 18) Ejiri and Ogawa, 19) Avignone,20) and others. 21) Reviews with emphasis on nuclear matrix elements have been made by Tomoda,22) Suhonen and Civitarese, 23) Simkovic and Faessler 24) and recent experimental data have been listed in a review by Tretyak and Zdesenko. 25)…”
Section: Double Beta Decays and Neutrinosmentioning
confidence: 84%
See 3 more Smart Citations
“…Recent works have been given in recent review articles, [1][2][3][4][5][6] and references therein. Recent experimental INVITED REVIEW PAPERS works have also been given in recent conference reports by Fiorini,17) Cremonesi, 18) Ejiri and Ogawa, 19) Avignone,20) and others. 21) Reviews with emphasis on nuclear matrix elements have been made by Tomoda,22) Suhonen and Civitarese, 23) Simkovic and Faessler 24) and recent experimental data have been listed in a review by Tretyak and Zdesenko. 25)…”
Section: Double Beta Decays and Neutrinosmentioning
confidence: 84%
“…32) The present CUORICINO 18) and NEMO III 32) are interesting in the search for the effective mass of around hm i ¼ 100 { 300 meV in the QD region. The recent oscillation studies have shown the flavor mixing and the mass-square differences of m, as discussed in §1.1.…”
Section: Experiments Of Double Beta Decaysmentioning
confidence: 95%
See 2 more Smart Citations
“…Even when taking the claimed evidence at face value the statistical significance is only about 97%, too weak for definitive conclusions. More sensitive experiments are needed and developed to explore this range of Majorana masses [47].…”
Section: Majorana Masses and Leptogenesismentioning
confidence: 99%